KEBIASAAN DAN KONSUMSI PANGAN SUKU BADUY - Dadang Sukandar; Eddy Setyo Mudjajanto (Jurnal Gizi dan Pangan, 2009)
The objectives of the study were: (1) to analyze the socio-economic and demographic characteristics of Baduy people; (2) to understand food habits and food consumption of Baduy people. This research  is an explorative and descriptive study on the socio-cultural aspects of nutrition and food system. The data required to meet the research objectives (social, economy, ecology, food habits, food consumption, health and nutritional status) were collected through a direct interview and discussion with respondents as well as a direct observation at the location of respondents. A sample size of 338 households was drawn from the population. The allocation of sample was 303 for Outer Baduy, 10 for Inner Baduy and 25 for Moslem Baduy. To obtain the data on the cultural aspects, history and  socio aspect of food, in-depth interviews was conducted with 19 key persons. The household energy and nutrient intake of Outer Baduy shows that the household energy and protein intake is 3,198 kcal and 95 g per capita. This energy and protein intake has surpassed the energy and protein sufficiency level (Recommended Dietary Allowances, RDA).  The energy and nutrient intake in Inner Baduy households shows that the household energy and protein daily intake per capita is 952 kcal and 17 g. This is far below the energy and protein sufficiency (Recommended Dietary Allowances, RDA).